2017
DOI: 10.1186/s40793-017-0240-8
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Kosakonia oryzae type strain Ola 51T

Abstract: Strain Ola 51T (=LMG 24251T = CGMCC 1.7012T) is the type strain of the species Kosakonia oryzae and was isolated from surface-sterilized roots of the wild rice species Oryza latifolia grown in Guangdong, China. Here we summarize the features of the strain Ola 51T and describe its complete genome sequence. The genome contains one circular chromosome of 5,303,342 nucleotides with 54.01% GC content, 4773 protein-coding genes, 16 rRNA genes, 76 tRNA genes, 13 ncRNA genes, 48 pseudo genes, and 1 CRISPR array.Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Furthermore, feeding dairy cows with the silage abundant in Clostridium would likely lead to the decrease of feed intake and a higher ketosis incidence ( Muck, 2010 ). Kosakonia and Pantoea are two new genera recently classified from the genus Enterobacter ( Li, 2016 ). The decline of these bacteria in the VA-treated silages might contribute to the reduction of DML and ammonia-N content.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, feeding dairy cows with the silage abundant in Clostridium would likely lead to the decrease of feed intake and a higher ketosis incidence ( Muck, 2010 ). Kosakonia and Pantoea are two new genera recently classified from the genus Enterobacter ( Li, 2016 ). The decline of these bacteria in the VA-treated silages might contribute to the reduction of DML and ammonia-N content.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have shown that the first flagellar system of DSM 16656 T (KFS1.a + KFS1.b) is expressed in liquid culture and upregulated in response to root exudates (Figure 3 ) indicating that KFS1 is used for swimming toward host plants; but the purpose of KFS2 has to be determined yet. Kosakonia oryzae Ola 51 T is closely related to K. radicincitans DSM 16656 T (Figure 1 ), possesses both flagellar systems (Figure 4 ) and like DSM 16656 T was found to be peritrichously flagellated (Li et al, 2017 ), but whether both flagellar systems contribute to formation of peritrichously inserted flagella still has to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…When detected, PBC6.1 colonized to ~2×10 5 CFU g –1 of root FW. Kosakonia sacchari is known to be associated with sugarcane ( Saccharum officinarum ) ( Chen et al , 2014 ; Gu et al , 2014 ) and sweet potato ( Ipomoea batatas ) ( Shinjo et al , 2016 ), while other members of the genus Kosakonia (formerly part of Enterobacter ) are beneficially associated with cereal crops including wheat ( Kämpfer et al ., 2005 ), sugarcane ( Taule et al , 2016 ; Beracochea et al , 2019 ; Taule et al , 2019 ), rice ( Oryza sativa ) ( Li et al , 2016 ; Li et al , 2017 ), and corn ( Kämpfer et al ., 2016 ). Using fluorescence microscopy of roots inoculated with a strain of PBC6.1 expressing RFP, we observed colonization of the corn root surface along the perimeters of cells ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%